Psychological Impact of Aerobic and Resistance Exercise in Patients with Heart Disease - Rayfal Fahmi Paturohman; Parhan Parhan; Muhammad Alieffirdho Zamroni; Muhammad Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
Aerobic and resistance exercises have been identified as effective interventions to improve the physical health of patients with heart disease. However, the psychological impact of these two types of exercise has not yet been studied in depth. This study aimed to evaluate the psychological effects of aerobic and resistance exercise in patients with heart disease, with a focus on levels of anxiety, depression, and quality of life. Through analysis of data from randomized clinical trials, it was found that both forms of exercise significantly reduced symptoms of anxiety and depression, and improved patients' quality of life. Aerobic exercise tends to be more effective in reducing anxiety, while resistance training shows better results in increasing self-confidence and mental resilience. These findings demonstrate the importance of integrating physical exercise into the rehabilitation program of cardiac patients to improve their psychological well-being.